Engaging Patients in Their Care Versus Obscurantism. Issue 3 (25th August 2014) - Tzeng, Huey‐Ming; Yin, Chang‐Yi; Fitzgerald, Kara
<x xml:space="preserve">Abstract</x> Problem Could engaging patients in their care be a means to oppose obscurantism? Obscurantism is defined by Merriam‐Webster as "the practice of keeping knowledge or understanding about something from people". Methods This paper discusses the importance of promoting patient engagement and emphasizes that patients and healthcare providers are equally important stakeholders in health care. Findings The discussion occurs in the context of hospital inpatient care as nurses play a critical role in patients' hospitalization experience, including engaging patients in their own care during hospital stays. Paternalism of healthcare providers is recognized as one of the main barriers to integrating the concepts of patient engagement and patient centeredness into every aspect of the care system. Promoting patient engagement is a two‐way responsibility, and it requires the cooperation of both patients and healthcare providers. Conclusions As scientists and healthcare providers, we have the duty to counter obscurantism by promoting understanding of the health of individual citizens and society at large. A culture change in healthcare systems toward being patient‐centric and placing value on patient engagement is warranted, and this change must come from healthcare providers. Patient‐centered tools that support patient engagement, patient portals, or personal health records are still needed.